Kemampuan abstraksi reflektif matematis siswa pada materi bangun ruang - Sutrisna, Nia; Pramuditya, Surya Amami; Raharjo, Jajo Firman; Setiyani, Setiyani (Mahesa Research Center, 2021)
This study aims to determine the ability of reflective mathematical abstraction which consists of the ability to apply concepts, the ability to make relationships between concepts to form new meanings, and the ability to manipulate abstract mathematical objects. This research is a qualitative research with type of case study. The sample used in this study was one senior high school student of class X. The method of collecting data to find the results of the study was to use a test instrument for building questions and interviews. These instruments are validated first using Expert Judgment Validation. The results obtained by indicator one and indicator two, student still find it difficult to understand the concept and choose which other concept is suitable to obtain a solution. Meanwhile, on the third indicator student can manipulate abstract mathematical objects. So that the student' mathematical abstraction ability is still quite good.